2002
DOI: 10.1177/004051750207200410
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Lyocell Fibers Spun from Isotropic Cellulose Dope in NMMO Monohydrate

Abstract: This article describes the physical properties of lyocell fibers spun from an isotropic cellulose spinning dope in N-methyl morpholine N-oxide (NMMO) monohydrate (IPS lyocell fibers). Wide angle x-ray diffraction (wAxD) experiments on the crimped fibers exhibit little difference in the crystal structure of IPS and Tencel lyocell fibers: both fibers reveal a cellulose II structure. However, the IPS lyocell fibers have a lower tensile modulus than Tencel by about 12.5%, although they have a similar tensile stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
(6 reference statements)
1
10
0
Order By: Relevance
“…The test methods for the fibres were in accordance to the British standards (British Standards, 1978) and a pre-tensioning of 0.5 cN/tex and crosshead speed of 10 mm/min were applied to the fibres. For more effective analysis the ends of the fibres specimens were glued to cardboard frames with epoxy resin (Chae et al, 2002) and then clamped in the Instron jaws. From the acquired data the mean tensile strength and elongation at break were reported.…”
Section: Determination Of Tensile Properties Of the Fibresmentioning
confidence: 99%
See 1 more Smart Citation
“…The test methods for the fibres were in accordance to the British standards (British Standards, 1978) and a pre-tensioning of 0.5 cN/tex and crosshead speed of 10 mm/min were applied to the fibres. For more effective analysis the ends of the fibres specimens were glued to cardboard frames with epoxy resin (Chae et al, 2002) and then clamped in the Instron jaws. From the acquired data the mean tensile strength and elongation at break were reported.…”
Section: Determination Of Tensile Properties Of the Fibresmentioning
confidence: 99%
“…The variation in the mechanical properties of the fibres with temperature was assessed by a DMA Q800 V7.5 instrument with the clamp mode in tension for film and fibres. In order to ensure firm clamping and minimum deformation of the specimen, the ends of the fibres specimens were glued to cardboard frames with epoxy resin and then introduced into the machine jaws (Chae et al, 2002). The analysis range was set with a standard temperature ramp programme, with heating of 3.00 °C/min from 25 °C to 200 °C and testing carried out at constant static strain and a frequency of 1 Hz.…”
Section: Determination Of Tensile Properties Of the Fibresmentioning
confidence: 99%
“…The high degree of crystallinity in lyocell is a consequence of higher orientation during stretching and formation of fibres; lyocell fibres have the thinnest and longest crystallites, even the amorphous regions are oriented along the fibre axis (Kreze and Malej 2003). Lyocell fibres spun from cellulose solution in N-methylmorpholine-N-oxide (NMMO) hydrate have proven commercially successful in textile and nonwoven products due to their excellent mechanical properties in the wet state, when compared with viscose rayon (Loubinoux and Chaunis 1987;Lenz et al 1993;Mortimer and Peguy 1996;Chae et al 2002). The manufacturing process is environmentally benign because the non-toxic, biodegradable NMMO solvent used is almost completely recycled (Woodings 1995;Albrecht et al 1997;Schuster et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, scientific investigation showed that superior moisture management of lyocell is essential as it keeps the body dry and generates a kind of natural air conditioning [2]. Lyocell fiber is famous for its better strength than any other man-made cellulosic fibres in wet state [3]. Lyocell fabric is very stable in washing and drying, easy to dye to deep vibrant colours and very comfortable to wear [4,5].…”
Section: Introductionmentioning
confidence: 99%